(untitled) (Revista Brasileira de Terapia Comportamental e Cognitiva, 2013)
This study evaluated the psychometric properties of the Brazilian version of the Personality Belief Questionnaire – Short Form (PBQ-SF). A sample of 700 college students answered to the Brazilian version of the PBQ-SF. The results showed good estimates of reliability (Cronbach’s alpha) of the PBQ-SF scales, indicating a significant association between the beliefs of each of the scales. The results of factor analysis of the PBQ-SF were similar to its original version. Overall, the findings provide support for the existence of factorial validity for the Brazilian version of the PBQ-SF, suggesting that it is a practical tool for the measurement of dysfunctional beliefs related to personality disorders